Database Management Mailing on UKM PALATIKA Using PHP and MYSQL - Ferry Fitriawan (Jurnal Sistem Informasi, 2010)
PALATIKA is the Student Activity Unit in Jakarta Campus STMIK STI & K,which moves in the field of Nature Lovers. During this recordingcorrespondence on SMEs Palatika for making the report is still done manuallythat is by way of note on the paper and then on the move through MicrosoftWord as the final ahead of the accountability report so many letters that are notlisted.Palatika should use a database that has a very important role in the processing ofdata such as data and correspondence. Through Correspondence Databasehandling this by using PHP (Personal Home Page) and MySQL is a goodsolution in solving the problems facing Palatika secretary during the time is tolaunch a secretarial job in preparing reports and correspondence and the receiptof correspondence.